2017
DOI: 10.1177/1934578x1701200418
|View full text |Cite
|
Sign up to set email alerts
|

Main Constituents and Antidiabetic Properties of Otholobium mexicanum

Abstract: Two phenols, bakuchiol (1) and 3-hydroxybakuchiol (2), and two isoflavone glycosides, daidzin (3) and genistin (4) were isolated from Otholobium mexicanum J. W. Grimes (Fabaceae). Moreover, the ability of the raw extract and isolated metabolites to inhibit the enzymes α-amylase and α-glucosidase was evaluated in vitro. In the α-amylase assay, the methanolic extract exhibited a moderate inhibitory activity with an IC50 of 470 μg/mL, while inhibition percentages of bakuchiol (1), 3-hydroxybakuchiol (2), and daid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Indeed, pancreatic and intestinal glucosidases are the key enzymes of dietary carbohydrate digestion, and inhibitors of these enzymes may be effective in slowing glucose absorption to suppress postprandial hyperglycemia. In this context, it is significant to mention that the extracts and phenolic or flavonoid contents of Gaiadendron punctatum [73], Muehlenbeckia tamnifolia [93], Oreocallis grandiflora [19], and Otholobium mexicanum [56], as well as trans-tiliroside (22) [53], prenyloxy eriodictyol (92), and rhamnetin (101) [96], showed enzymatic inhibitory activity that was comparable or superior to acarbose, which is a drug that is currently used in the treatment of diabetes mellitus. Therefore, these results should promote studies on determining whether these hypoglycemic products can become sources of new antidiabetic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, pancreatic and intestinal glucosidases are the key enzymes of dietary carbohydrate digestion, and inhibitors of these enzymes may be effective in slowing glucose absorption to suppress postprandial hyperglycemia. In this context, it is significant to mention that the extracts and phenolic or flavonoid contents of Gaiadendron punctatum [73], Muehlenbeckia tamnifolia [93], Oreocallis grandiflora [19], and Otholobium mexicanum [56], as well as trans-tiliroside (22) [53], prenyloxy eriodictyol (92), and rhamnetin (101) [96], showed enzymatic inhibitory activity that was comparable or superior to acarbose, which is a drug that is currently used in the treatment of diabetes mellitus. Therefore, these results should promote studies on determining whether these hypoglycemic products can become sources of new antidiabetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Bakuchiol (24), hydroxybakuchiol (25), daidzin (26), and genistin (27) (Figure 5) were isolated from a leaf methanolic extract and identified using NMR spectroscopy [56].…”
Section: W (Grimes) Culenmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a previous study has confirmed that orally administering bakuchiol reduces blood glucose levels in db/db mice with type 2 diabetes [ 15 ]. A compound called 3-hydroxybakuchiol (HYD) with a similar structure to bakuchiol has been discovered in Otholobium mexicanum, showing potential anti-diabetic activity [ 17 , 18 ]. This suggested a potential anti-diabetic activity of HYD.…”
Section: Introductionmentioning
confidence: 99%
“…It is known with the vernacular name of "mosquera", the exudate latex of the stem bark is yellow, and it is used to eliminate warts and to treat wounds, sores, and ulcers [34]. The diabetes is one of the major health problems in Ecuador [35,36] where the people commonly use medicinal plants to control this metabolic disease. In addition, finding new antibacterial agents is a big issue in medicinal chemistry because increasing resistance to antibiotic agents that are currently in use.…”
Section: Introductionmentioning
confidence: 99%